MED8 is related to tumor immunity and has predictive value in the prognosis and treatment of glioma - Jingyi Yang; Bin Li; Xinghai Zhang; Yufeng Li; Hao Yuan (Discover Oncology)
Abstract Background Mediator complex subunit 8 (MED8) is the main regulator of RNA polymerase. Its expression is associated with a poor prognosis and tumor immune features in many tumors, but the role of MED8 in gliomas is unknown. Methods In this study, bioinformatics analysis was used to explore the effect of MED8 in gliomas and the correlation between MED8 and tumor immune features and the response to immunotherapy in gliomas. The expression of MED8 in cell lines was studied by qPCR. Results Studies show increased expression of MED8 is associated with poor prognosis in glioma. Cox regression analysis and survival analysis revealed that MED8 is an independent prognostic factor in gliomas, and patients with high expression of MED8 have a poor prognosis. Functional analysis revealed that there was a close relationship between MED8 expression and tumor immune features, and there was a correlation between MED8 expression and tumor-associated macrophages (TAMs) levels. In addition, glioma patients with low expression of MED8 were more sensitive to anti-PD-1/anti-CTLA4 immunotherapy, while patients with high expression of MED8 were more sensitive to temozolomide (TMZ). Conclusion These results show that MED8 is a marker of prognosis and immunotherapy/chemotherapy response in glioma and a target of anti-TAMs immunotherapy for glioma.